2017
DOI: 10.1016/j.orgel.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Solution modification of PEDOT:PSS inks for ultrasonic spray coating

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To date, the use of ultrasonic spray coating for fabricating solar cells and modules has not been limited to just the perovskite active layers. [5g,7b,13f,16] It has also been equally valuable in fabricating HTLs [17] and ETLs. [5f,18] Finally, recent advances have also featured fully spray-cast PSCs, i.e., all key components including the HTL/perovskite layer/ETL were fabricated by spray coating.…”
Section: Ultrasonic Spray Coatingmentioning
confidence: 99%
“…To date, the use of ultrasonic spray coating for fabricating solar cells and modules has not been limited to just the perovskite active layers. [5g,7b,13f,16] It has also been equally valuable in fabricating HTLs [17] and ETLs. [5f,18] Finally, recent advances have also featured fully spray-cast PSCs, i.e., all key components including the HTL/perovskite layer/ETL were fabricated by spray coating.…”
Section: Ultrasonic Spray Coatingmentioning
confidence: 99%
“…Spray-coating is a technique that we have investigated extensively to fabricate both organic and perovskite , photovoltaic devices. In comparison with other scalable techniques, spray deposition has two advantages.…”
Section: Basic Principles Of Perovskite Spray-coatingmentioning
confidence: 99%
“…11 Such additives have also been used to suppress dewetting of PEDOT:PSS films, and thus, this approach could be applied more generally when formulating semiconductor inks for spraycoating applications. 43 Note, however, that it will be important to explore the extent to which such materials can be used (even within the perovskite active layer) to improve processing and film morphology without compromising electronic functionality.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…This effect appeared to be promoted by the addition of dopant molecules to the spiro-OMeTAD to improve its conductivity; however, it was found that dewetting could be largely suppressed by the use of viscosity modifiers . Such additives have also been used to suppress dewetting of PEDOT:PSS films, and thus, this approach could be applied more generally when formulating semiconductor inks for spray-coating applications . Note, however, that it will be important to explore the extent to which such materials can be used (even within the perovskite active layer) to improve processing and film morphology without compromising electronic functionality.…”
mentioning
confidence: 99%